An ELISA-based method for rapid genetic screens in Drosophila. - Jay, T.R.; Kang, Y.; Jefferson, A.; Freeman, M.R. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Drosophila is a powerful model in which to perform genetic screens, but screening assays that are both rapid and can be used to examine a wide variety of cellular and molecular pathways are limited. Drosophila offer an extensive toolbox of GFP-based transcriptional reporters, GFP-tagged proteins, and driver lines, which can be used to express GFP in numerous subpopulations of cells. Thus, a tool that can rapidly and quantitatively evaluate GFP levels in Drosophila tissue would provide a broadly applicable screening platform. We developed a GFP-based enzyme-linked immunosorbent assay (ELISA) that can detect GFP in Drosophila lysates collected from whole animals and dissected tissues across all stages of Drosophila development. We demonstrate that this assay can detect membrane-localized GFP in a variety of neuronal and glial populations and validate that it can identify genes that change the morphology of these cells, as well as changes in STAT and JNK transcriptional activity. We found that this assay can detect endogenously GFP-tagged proteins, including Draper, Cryptochrome, and the synaptic marker Brp. This approach is able to detect changes in Brp-GFP signal during developmental synaptic remodeling, and known genetic regulators of glial synaptic engulfment could be identified using this ELISA method. Finally, we used the assay to perform a small-scale screen, which identified Syntaxins as potential regulators of astrocyte-mediated synapse elimination. Together, these studies establish an ELISA as a rapid, easy, and quantitative in vivo screening method that can be used to assay a wide breadth of fundamental biological questions.